Atomic spectrometry update: review of advances in the analysis of metals, chemicals and materials. Issue 11 (25th October 2022) - Carter, Simon; Clough, Robert; Fisher, Andy; Gibson, Bridget; Russell, Ben
Abstract : This review covers advances in the analysis of advanced materials, metals, fuels and lubricants, nanostructures, ceramics, refractories, organic and inorganic chemicals, catalysts and nuclear materials by a range of techniques including X-ray, ICP, LIBS, mass spectrometry, synchrotron-based techniques, plus non-destructive and ablation surface techniques. Abstract : This update covers the literature published between approximately June 2021 and May 2022 and is the latest part of a series of annual reviews. It is designed to provide the reader with an overview of the current state of the art with respect to the atomic spectrometric analysis of various metals, chemicals and materials. These materials include ferrous and non-ferrous metals, glasses, polymers, ceramics, engineered nanostructures, fuels, nuclear materials, building materials, catalysts and electronic components. Also included is the analysis of forensic samples such as explosives and gunshot residue. It is not a comprehensive review of all papers that have used an atomic spectrometric technique. Instead, it includes only those papers that have some novelty through making an advance in either knowledge or the application of atomic spectrometry. Those papers that maximise the information gleaned from analytical data, e.g. the provenance of cultural heritage or forensic samples, through the use of chemometric analysis will also be included.